Keanekaragaman Jenis dan Kerapatan Vegetasi Hutan Pantai di Selatan Pulau Sumbawa, Kecamatan Labangka, Kabupaten Sumbawa: Species Diversity and Density of Coastal Forest in the South of Sumbawa Island, Labangka Subdistrict, Sumbawa District - Eni Hidayati; Dedi Syafikri; Muhammad Reza Ramdhani; Nandita Pasya Salsabila (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
in Labangka Village in the South of Sumbawa Island is very important considering that this village is directly facing the Indian Ocean. In addition, the development of aquaculture in this village also requires knowledge of the vegetation that makes up the coastal forest so that appropriate management and monitoring activities can be planned. This study aims to identify the types of vegetation in coastal forest ecosystem in Labangka Village at four stations, namely in locations where super-intensive aquaculture will be built. The method used is the analysis of Importance Value Index and Normalized Differentiation Vegetation Index. The results of the study were as follows: Station 1 (27 species, dominated by Pongamia pinnata with an IVI of 185.64% for the tree level and IVI of 114.58% for the seedling level), Station 2 (9 species, dominated by P. pinnata INP of 214.16 % for the tree level and Leucaena leucocephala IVI 96.49% for the seedling level), Station 3 (18 species dominated by the pes-caprae formation type and shrubs, namely S. taccada, P. tectorius, and Heliotropium foertherianum), Station 4 (19 species dominated by shrubs namely S. taccada, Pandanus tectorius, and H. foertherianum and shrubs (L. camara and C. bonduc).The NDVI at observation stations ranged from -0.091 (sparse) to 0.543 (dense).